2012
DOI: 10.1111/j.1399-3038.2011.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental evidence that early‐life farm environment influences regulation of immune responses

Abstract: Background: In mammals, early-life environmental variations appear to affect microbial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 12 publications
4
39
1
2
Order By: Relevance
“…Outdoor rearing was associated with the establishment of diverse microbiota and immune function, whereas indoor-housed animals showed altered gut microbiota, increased expression of proinflammatory genes, and reduced numbers of T reg cells (80,81).…”
Section: Home and Its Surroundingmentioning
confidence: 99%
“…Outdoor rearing was associated with the establishment of diverse microbiota and immune function, whereas indoor-housed animals showed altered gut microbiota, increased expression of proinflammatory genes, and reduced numbers of T reg cells (80,81).…”
Section: Home and Its Surroundingmentioning
confidence: 99%
“…In other research, prostration has been identified as a behaviour that indicates "stress" (Dybkjaer et al 2006). This type of conduct has been observed more frequently during the first 12 h of transport (2.8%) than in the following 12 h (0.3%) , and is also observed more often during the first day that piglets spend in weaning corrals (0.49%), though it decreases (0.29%) on the second and third days that the piglet stays in that area (Lewis et al 2012). On the basis of these findings, the authors posit that the increase in prostration, the reduced number of piglets that sit, and the establishment of new hierarchies may be signals indicating that the piglets have become habituated to some of the elements of the shipping environment (Berry and Lewis 2001).…”
Section: Duration Of Transportmentioning
confidence: 89%
“…In addition, the season of the year can affect piglet behaviour during transport, as it has been observed that the number of piglets that fight inside the truck in the summer (39) is greater than in wintertime (just 3). This finding might indicate that in winter thermoregulation takes priority for the piglets, while certain social behaviours -like establishing hierarchies -take a back seat Lewis et al 2012). In this regard, Lewis (2008) mentions that the average body temperature measured on the surface of the ear in summer (36.2 °C) was significantly higher than the temperatures measured in autumn (27.0 °C) and winter (23.1 °C).…”
Section: Temperature During Transportmentioning
confidence: 97%
See 2 more Smart Citations